Variables involved in the development of social resilience in sustainable economies: From individual resilience to societies' resilience - Moya Velasco, Jorge; Goenechea Domínguez, María (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The aim of this article is to objectify several variables involved in the growth of the social resilience. To do this, it has been made a conceptual approximation of the term that includes the capacity of a community for, overcoming difficulties, adapting, and transforming itself. After analysing the most relevant studies and explaining the difficulties for modelling, we have grouped the relationships that potentially improve the social resilience. We conclude that, through a process of social intelligence, it is possible to guide the development of our economies into spaces of innovation and transformability that will improve the social resilience.